DIGEST uno standard di interscambio per dati geografici digitali - Beaulieu, Pierre J.C.; Dohmann, Herman A.; Amadio, Gianfranco (GEOmedia, 2016)
DIGEST uno standard di interscambio per dati geografici digitali